Measurement of Lead Isotopes in Snow and Ice from Law Dome and other sites in Antarctica to characterize the Lead and seek evidence of its origin - Vallelonga, Paul Travis (Curtin University, 2002)
Human activities such as mining and smelting of lead (Pb) ores and combustion of alkyllead additives in gasoline have resulted in extensive global Pb pollution. Since the late 1960's studies of polar ice and snow have been undertaken to evaluate the extent of anthropogenic Pb emissions in recent times as well as to investigate changes in anthropogenic Pb emissions in the more distant past. The polar ice sheets have been used to investigate Pb pollution as they offer a long-term record of human activity located far from pollution sources and sample aerosol emissions on a hemispheric scale. Lead isotopes have been previously used to identify sources of Pb in polar snow and ice, while new evaluations of Pb isotopic compositions in aerosols and Pb ore bodies allow more thorough evaluations of anthropogenic Pb emissions. Lead isotopic compositions and Pb and Barium (Ba) concentrations have been measured in snow and ice core samples from Law Dome, East Antarctica, to produce a detailed pollution history between 1530 AD and 1989 AD. Such a record has been produced to evaluate changes in anthropogenic Pb emission levels and sources over the past 500 years, to determine when industrial (anthropogenic) activities first began to influence Antarctica and also to investigate natural Pb fluxes to Antarctica. Additional samples were also collected from Law Dome snow and ice cores to respectively investigate seasonal variations in Pb and Ba deposition, and the influence of the 1815 AD volcanic eruption of Tambora, Indonesia. All samples were measured by thermal ionisation mass spectrometry, for which techniques were developed to reliably analyse Pb isotopic compositions in Antarctic samples containing sub-picogram per gram concentrations of Pb.Particular attention was given to the quantity of Pb added to the samples during the decontamination and sample storage stages of the sample preparation process. These stages, including the use of a stainless steel chisel for the decontamination, contributed ~5.2 pg to the total sample analysed, amounting to a concentration increase of ~13 fg g-1. In comparison, the mass spectrometer ion source contributed typically 89 +/- 19 fg to the blank, however its influence depended upon the amount of Pb available for analysis and so had the greatest impact when small volumes of samples with a very low concentration were analysed. As a consequence of these careful investigations of the Pb blank contributions to the samples, the corrections made to the Pb isotopic ratios and concentrations measured are smaller than previously reported evaluations of Pb in Antarctica by thermal ionisation mass spectrometry. The data indicate that East Antarctica was relatively pristine until -1884 AD, after which the first influence of anthropogenic Pb in Law Dome is observed. "Natural", pre-industrial, background concentrations of Pb and Ba were - 0.4 pg/g and - 1.3 pg/g, respectively, with Pb isotopic compositions within the range 206Pb/207Pb = 1.20 - 1.25 and 208Pb/207Pb = 2.46 - 2.50 and an average rock and soil dust Pb contribution of 8-12%. A major pollution event was observed at Law Dome between 1884 and 1908 AD, elevating the Pb concentration fourfold and changing 206Pb/207Pb ratios in the ice to ~1.12. Based on Pb isotopic systematics and Pb emissions statistics, this was attributed to Pb mined at Broken Hill and smelted at Broken Hill and Port Pirie, Australia.Anthropogenic Pb inputs to Law Dome were most significant from ~1900 to 1910 and from ~1960 to 1980. During the 20th century, Ba concentrations were consistently higher than "natural" levels. This was attributed to increased dust production, suggesting the influence of climate change and/or changes in land coverage with vegetation. Law Dome ice dated from 1814 AD to 1819 AD was analysed for Pb isotopes and Pb, Ba and Bismuth (Bi) concentrations to investigate the influence of the 1815 AD volcanic eruption of Tambora, Indonesia. The presence of volcanic debris in the core samples was observed from late-1816 AD to 1818 AD as an increase in sulphate concentrations and electrical conductivity of the ice. Barium concentrations were approximately three times higher than background levels from mid-1816 to mid1818, consistent with increased atmospheric loading of rock and soil dust, while enhanced Pb/Ba and Bi/Ba ratios, associated with deposition of volcanic debris, were observed at mid-1814 and from early-1817 to mid-1818. From the results, it appeared likely that Pb emitted from Tambora was removed from the atmosphere within the 1.6 year period required to transport aerosols to Antarctica. Increased Pb and Bi concentrations observed in Law Dome ice ~1818 AD were attributed to either increased heavy metal emissions from Mount Erebus, or increased fluxes of heavy metals to the Antarctic ice sheet resulting from climate and meteorological modifications following the Tambora eruption.A non-continuous series of Law Dome snow core samples dating from 1980 to 9185 AD were analysed to investigate seasonal variations in the deposition of Pb and Ba. It was found that Pb and Ba at Law Dome do exhibit seasonal variations in deposition, with higher concentrations of Pb and Ba usually observed during Summer and lower concentrations of Pb and Ba usually observed during the Autumn and Spring seasons. At Law Dome, broad patterns of seasonal Pb and Ba deposition are evident however these appear to be punctuated by short-term deposition events or may even be composed of a continuum of short-term deposition events. This variability suggests that complex meteorological systems are responsible for the transport of Pb and Ba to Law Dome, and probably Antarctica in general.